READING ACHEBE’S THINGS FALL APART FROM CÉSAIRE’S PERSPECTIVE ON ANTICOLONIALISM - Tuaderu, Yohanes (Lire Journal (Journal of Linguistics and Literature), 2024)
This research aims to obtain a deep notion of what stands beyond one of Achebe’s prominent African trilogies – Things Fall Apart – from the concept of anticolonialism promoted by Aimé Césaire. It examines two main subject matters i.e.; the reason why African people struggle so hard to oppose the oppression of the colonizers and what efforts they develop to react to the bad treatment. The harassment of human values - what Césaire called "thingification", trampled culture, damaged socio-cultural foundations, destroyed native religions, and confiscated ancestral inherited lands have apparently become the trigger for the struggle against colonialism. Meanwhile, the real way and effort made to fight the arrogance of the colonialists was to strengthen cultural identity and maintain the noble values that had united all tribes. In this way, the Igbo tribe and the Nigerian people finally gained their independence on October 1, 1960 - 2 (two) years after the novel Things Fall Apart was published.